0677 Patient Preferences On Initiating Treatment With Continuous Positive Airway Pressure. (27th May 2020) - Borker, P V; Wyland, C; Patel, S R
Abstract: Introduction: Clinical guidelines recommend continuous positive airway pressure (CPAP) therapy be initiated in patients with obstructive sleep apnea (OSA) either at home using an auto-titrating device or following manual titration in the sleep laboratory. Patient preference between these two options is unknown. Methods: Patients newly prescribed CPAP therapy for the treatment of OSA at an academic sleep medicine clinic were surveyed by telephone within one month of initiating treatment. Data on demographics, disease severity and CPAP adherence were obtained from the medical record. Results: A total of 75 participants (56% male, mean age 52±15 yrs, 48% moderate to severe OSA) were surveyed. Physicians prescribed home initiation of CPAP in 51%, lab initiation in 23%, and allowed the patient to choose in 27% of cases. Overall, 67% of participants (95% CI [56%-77%]) reported preference for home initiation. Preference for home initiation did not vary by age, sex, AHI, degree of sleepiness, or type of diagnostic study (home vs. lab sleep study) performed (p>0.10 for all). Convenience (44%) and starting treatment faster (44%) were the most common reasons provided for those favoring home initiation, while sleep technician availability (40%), optimization of pressure settings (32%), and ability to try multiple masks (28%) were cited by those favoring lab initiation. The prevalence of CPAP adherence at 90 days tended to be higher in those whose treatment was initiated aligned to preference (79% in those whose treatment initiation was concordant with preference vs. 64% in those whose treatment initiation was discordant, p=0.16). Conclusion: Overall, two-thirds of patients with OSA prefer initiation of CPAP be done at home. This preference does not vary by demographics, OSA severity or diagnostic modality. Initiating treatment concordant with patient preference may lead to greater adherence. Support: American Thoracic Society Academic Sleep Pulmonary Integrated Research/Clinical (ASPIRE) Fellowship, K24 HL127307